Predictors for the recurrent febrile seizures after the first complex febrile seizures - Conny Tanjung; Irawan Mangunatmadja; Sudigdo Sastroasmoro; I. Budiman (Paediatrica Indonesiana, 2006)
Background Complex febrile seizures (CFS) have been shownto be related to recurrence and epilepsy. Many studies were doneto determine the predictors of recurrence in both simple and com-plex febrile seizures. To our knowledge until now there is no pub-lished data that specially looks for predictors of recurrence after afirst CFS.Objective To find out clinical and demographical characteristicsof a first CFS and to define the predictors for the recurrent febrileseizures.Methods Prospective survival analysis study was done in chil-dren with first CFS who visited Cipto Mangunkusumo Hospital,Jakarta, over 14 months periods. The predictors for developmentof recurrence were analyzed by SPSS for Windows 11.5 usingKaplan-Meier test and Cox regression model with a level of signifi-cance <0.05.Results There were 62 subjects completed this study. Male-to-female ratio was 1.4:1. The mean age at onset was 18.2 months.Recurrence occurred in 9 subjects (14.5%). Body temperaturebetween 38-38.5Â°C (7 of 26 subjects, P=0.02), upper motor neu-ron type of delayed development (3 of 7 subjects, P=0.03), andepileptic history in the family (2 of 2 subjects, P<0.05) were asso-ciated with recurrence in bivariate analysis. In multivariate analy-sis only body temperature between 38-38.5Â°C (HR 1.6, 95% CI1.0;23.9) and epileptic history in the family (HR 16.9, 95% CI2.8;101.4) were identified as predictors.Conclusion Low body temperature at the first seizures and epi-leptic history in the family were independent predictors for the re-currence after a first CFS